SHORT- AND LONG-TERM OUTCOMES OF CORONARY REVASCULARISATION IN PATIENTS WITH SEVERE LEFT VENTRICULAR DILATATION. (8th October 2012) - Wang, Xiao; Nie, Shaoping; Ma, Changsheng; Liu, Xiaohui; Dong, Jianzeng; Du, Xin; Hu, Rong; Kang, Junping; Lv, Qiang; Liu, Xinmin; Chen, Fang; Lv, Shuzheng; et al.
Abstract : Objectives: Patients with coronary artery disease accompanied by severe left ventricular dilatation (LVD) are at higher risk for heart failure and death. However, their clinical and angiographic profiles, short- and long-term outcomes after revascularisation are unknown. Methods: A total of 4283 patients (median age 60.0 years; 77.4% male) undergoing coronary revascularisation in our centre from July 2003 to September 2005 were stratified according to end-diastolic dimension (EDD). Patients with severe LVD (EDD>70 mm), mild/moderate LVD (EDD 52.7 mm to 70.0 mm in males, EDD 48.3 mm to 70.0 mm in females), and no LVD (EDD<52.7 mm in males, EDD<48.3 mm in females) was compared for outcome analysis. Results: Patients with severe LVD had more complex lesions (eg, chronic total occlusions, multi-vessel disease) with more prior myocardial infarction, valvular impairments and renal dysfunction (all p<0.001). Patients successfully discharged were followed up for a median of 548 (455–669) days. Severe LVD was significantly associated with increased in-hospital mortality (5.4% vs 1.6% vs 1.0%, p<0.001) and composite ischaemia (6.9% vs 2.5% vs 2.1%, p<0.001) compared with mild/moderate LVD and no LVD groups. By multivariable analysis, severe LVD was a significant independent predictor of in-hospital (HR 1.858, 95% CI 1.323 to 2.611, p<0.001) and follow-up mortality (HR 1.697, 95% CI 1.253 to 2.298, p=0.001) after revascularisation. Conclusions: Patients with severe LVD have more co-morbidities and complex coronary lesions. Severe LVD in patients undergoing coronary revascularisation was an independent predictor of early and late mortality and adverse ischaemic outcomes.